Specyfika zarządzania projektami finansowanymi z Europejskiego Funduszu Społecznego w państwowych szkołach wyższych - Kwiatkowska-Ciotucha, Dorota (Specificity of managing projects financed by European Social Fund provided by public universities, 2007)
The paper presents results of the analyses of specific aspects of management problems connected with projects’ realization. The assessment is based on projects financed from the European Social Funds in Poland during the period of 2004-2006. In the research some barriers and threads arising in particular step of project’s realization are discussed. The author focused on projects, which are realized by public university. For the illustration, some experiences from project realization in Wrocław University of Economics are presented and discussed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 310-321